Economic recovery in Africa and its determinants - Badiane, Ousmane; Collins, Julia; Diao, Xinshen; Ulimwengu, John M. (International Food Policy Research Institute, 2015)
In this paper, we review the characteristics of Africa’s recent growth performance, discussing the drivers, future outlook, and potential risks. The roles of governance and policy reforms, investment, and the management of mining and other natural resource sectors are highlighted. In the first section, we analyze economic growth and agricultural productivity trends since independence. As economic performance by African countries has changed drastically, we assess the current performance against the long-term growth trajectory of African economies since the 1960s. Given the breadth of the recovery process, we also look for evidence of convergence among African economies as well as between African economies and the rest of the world. In section 2 we review the evolution of economic development and growth policies and strategies in Africa. We compare Africa’s reform experience with that of one of the successful emerging economies, China, to examine the factors contributing to the success of policy reforms. This evaluation is followed by an econometric analysis of the drivers of growth in section 3. The final section summarizes the evidence and provides recommendations for sustaining agricultural and economic growth and avoiding potential risks.